2001
DOI: 10.2337/diacare.24.4.726
|View full text |Cite
|
Sign up to set email alerts
|

α-Dicarbonyls Increase in the Postprandial Period and Reflect the Degree of Hyperglycemia

Abstract: OBJECTIVE -Chronic hyperglycemia is known to increase tissue glycation and diabetic complications, but controversy exists regarding the independent role of increased postprandial glucose excursions. To address this question, we have studied the effect of postprandial glycemic excursions (PPGEs) on levels of methylglyoxal (MG) and 3-deoxyglucosone (3-DG), two highly reactive precursors of advanced glycation end products (AGEs).RESEARCH DESIGN AND METHODS -We performed 4-month crossover studies on 21 subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
2
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 65 publications
(36 reference statements)
9
125
2
6
Order By: Relevance
“…This suggests involvement of additional oxidative mechanisms in its formation. In patients with type 1 diabetes, Beisswenger et al (31) observed an increase in 3DG within 2 h, whereas in our pilot study in patients with type 2 diabetes we did not observe a rise in 3DG after the first meal (21).…”
Section: Figure 2-relations Between Postprandial Changes Of the Oxidicontrasting
confidence: 40%
“…This suggests involvement of additional oxidative mechanisms in its formation. In patients with type 1 diabetes, Beisswenger et al (31) observed an increase in 3DG within 2 h, whereas in our pilot study in patients with type 2 diabetes we did not observe a rise in 3DG after the first meal (21).…”
Section: Figure 2-relations Between Postprandial Changes Of the Oxidicontrasting
confidence: 40%
“…However, the possibility that postprandial hyperglycaemia increases oxidative stress and inflammation in healthy subjects has previously been reported [12,13]. Furthermore, evidence showing that modulation of postprandial hyperglycaemia by diet or an insulin analogue in type 2 diabetes [25][26][27], and by pramlintide [28] in type 1 diabetes, is accompanied by a significant decrease of oxidative stress, while nuclear factor kappa B activation is decreased when controlling postprandial hyperglycaemia by acarbose [24], convincingly suggests that the effect of S21403 on postprandial oxidative stress and inflammation is related to its ability to reduce postprandial hyperglycaemia.…”
Section: Discussionmentioning
confidence: 98%
“…The recruitment of diabetic patients for this study has been described previously [10] and patient characteristics are summarised in Table 1. Twenty-one type 1 diabetic patients, with normal creatinine clearance (although three patients had microalbuminuria) and no other microvascular complications, and 12 normal healthy control subjects were recruited.…”
Section: Subjectsmentioning
confidence: 99%
“…Urinary and plasma creatinine were determined by colorimetric assay (diagnostic kit 510; Sigma). Fasting plasma glucose (FPG), mean daily plasma glucose (24hG) and postprandial changes in plasma glucose (PPG) were assessed as described previously [10].…”
Section: Measurement Of Protein Glycation Oxidation and Nitration Admentioning
confidence: 99%